The Establisment of Caring Community Through TB Care Muhammadiyah at Puskesmas Tamansari Tasikmalaya City - Nina Pamela Sari; Asep Muksin; Putri Nur Anjeli; Haeya Firda Nisa; Eri Nugraha (AbdimasMu UMTAS, 2022)
Tuberculosis is an infectious disease whose number is still increasing in Indonesia, especially in Mulyasari Village, Tamansari District, Tasikmalaya City. TB incidence in Tamansari as of November 2020 reached 58 people, 3 people died and 1 person experienced drug resistance. Muhammadiyah is an Islamic da'wah movement for amar ma'ruf nahi munkar whose one of its da'wah movements is concerned with social humanitarian movements in the health sector. One of the health services that continues to be developed by Muhammadiyah is service and counseling to the community about TB disease and socialization of the use of TB Comprehensive PMO guidelines which can improve the cognitive, affective and psychomotor abilities of TB PMO which have an impact on increasing public awareness of TB disease. This program is implemented through counseling to cadres, religious leaders and PMOs in the work area of ??the Tamansari Health Center about TB disease and socialization of the use of TB Comprehensive PMO guidelines. Tamansari Health Center consists of 4 sub-districts, namely Mulyasari village, Sukahurip village, Setyawargi village and Setyamulya village. The results of this community service are an increase in the knowledge of cadres, PMOs and religious leaders about TB control and the formation of the TB Care Muhammadiyah management where in each disctrict there are 4 Muhammadiyah branch managers who collaborate with the village cadre coordinator to participate in monitoring the treatment of TB patients in the Tamansari area.